Applying the environmental flow components approach to the River Murray in South Australia. Issue 2 (3rd July 2017) - Souter, Nicholas J.
ABSTRACT: River regulation has degraded the River Murray's riverine ecosystems. Environmental flows are now being delivered to restore these ecosystems to a more natural, pre-regulation state. To guide the development of environmental flow recommendations, I calculated 28 Environmental Flow Components for the River Murray in South Australia, comparing simulated flow data for natural and present conditions. Regulation has caused complex changes to the rivers' hydrology. Under present conditions, the inter-annual frequency of extreme low flows (<4150 ML/day) and high flow pulses (15, 000–55, 000 ML/day) has increased, whilst for small floods (55, 000–100, 000 ML/day) and large floods (>100, 000 ML/day) frequency has declined. The magnitude of low flows (4150–15, 000 ML/day) has been reduced for all months, and extreme low flows and high flow pulses occur later in the year. The duration of high flow pulses, and both small and large floods, have also declined under present conditions. Restoring more natural extreme low flows and high flow pulses will require new events to be engineered, whilst environmental water can be used to enhance monthly low flows and small floods. In addition to providing environmental flows, changes to river operations, particularly instituting weir pool manipulation, is required to maximise ecological outcomes.